Franklin and Friends ([Tasmania] : Sturm, Jonathan)
An on-line magazine about the music, culture, poetry, short stories, photographs, art, architecture, craft, history and more of a small community in southern Tasmania
Mode of access: Internet via World Wide Web. Available at: http://odi.statelibrary.tas.gov.au
Keywords: Franklin (Tas.)